Bebarongan's New Creation Composition “Inguh” | Komposisi Kreasi Baru Bebarongan “Inguh” - I Ketut Partha (GHURNITA: Jurnal Seni Karawitan, 2021)
The creation of the Bebarongan "Inguh" musical is to realize the stylist's imagination about the feeling of chaos as a motivation to encourage the achievement of a new creative musical work. The stylist gets the idea from his own experience, which reflects himself to make a bebarongan percussion creation, through a bebarongan percussion using the gamelan Semar Pegulingan saih pitu. This work will be carried out in three stages taken from the concept of M. Hawkins in the book Creathing Troug Dance. These are the exploration stage, the experimental stage, and the last stage is the formation stage. This percussion bebarongan creation refers to the concept of gamelan creativity. This creation still refers to existing traditions or uses existing standards. This work is realized through a process and using existing patterns and patterns of strokes. As a suggestion, it is necessary to explore the uniqueness of Balinese musical which provides a stimulus to work, in order to provide a wealth for all who will be creative in the field of musical art, along with the development of the times and the human mindset, this is worth pondering for those who are involved in the field of musical art.